2016
DOI: 10.1177/0266666915599586
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Issues in B2C E-commerce

Abstract: B2C e-commerce is one of the fastest growing industries worldwide. A lot of studies were carried out by both scholars and practitioners in order to assess online consumers’ behavioral issues in B2C e-commerce platforms. This paper aims to organize and classify the accumulated literature on B2C e-commerce in order to determine less-researched areas and provide future research directions. For that purpose 208 peer-reviewed articles from 71 journals published between 2005 and 2014 were retrieved and analyzed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 206 publications
1
11
0
Order By: Relevance
“…Relatedly, a more specific definition of e-commerce is provided by Turban, King, Lee, Liang and Turban (2010) who state that "e-commerce is the process of buying, selling, transferring and exchanging products and/or information using computer networks mainly the Internet and Intranets." This is in line with Huseynov & Yildirim (2016) who define e-commerce as the process of conducting businesses through computer networks. Hence, e-commerce is about firms conducting business while utilizing a network of ICT, particularly the internet.…”
Section: Introduction and Problem Statementsupporting
confidence: 83%
“…Relatedly, a more specific definition of e-commerce is provided by Turban, King, Lee, Liang and Turban (2010) who state that "e-commerce is the process of buying, selling, transferring and exchanging products and/or information using computer networks mainly the Internet and Intranets." This is in line with Huseynov & Yildirim (2016) who define e-commerce as the process of conducting businesses through computer networks. Hence, e-commerce is about firms conducting business while utilizing a network of ICT, particularly the internet.…”
Section: Introduction and Problem Statementsupporting
confidence: 83%
“…Liu, Li, Peng, Lv, & Zhang, 2015;Nakano & Kondo, 2018;Pandey, Chawla, & Venkatesh, 2015;Swinyard & Smith, 2003;Ye, Li, & Gu, 2011) were conducted and the results showed that a general consumer audience is composed of different consumer groups with different psychographic and behavioral characteristics. Despite the common agreement on the existence of different online consumer typologies, extensive literature review showed that while accessing consumers' behaviors in online shopping platforms, most of the existing studies ignored this fact (Huseynov & Yıldırım, 2016a). Therefore, the general conclusions made by these studies about consumers' behaviors, attitudes, and decision-making processes might not be valid for broad online consumer audience and might not reflect actual behavior of different consumer segments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a great deal of researches (Ariffin, Mohan, & Goh, 2018;Changchit, Cutshall, Lonkani, Pholwan, & Pongwiritthon, 2018;Chiu, Wang, Fang, & Huang, 2014;R. Davis, Lang, & Diego, 2014;Dwivedi, Rana, Jeyaraj, Clement, & Williams, 2017;Fortes & Rita, 2016;Huseynov & Yıldırım, 2016a; Y. J. Lim, Osman, Salahuddin, Romle, & Abdullah, 2016;Pappas, Kourouthanassis, Giannakos, & Chrissikopoulos, 2017;Pelaez, Chen, & Chen, 2019;Smith et al, 2013;O.…”
Section: Introductionmentioning
confidence: 99%
“…The B2B e-commerce model enables companies to use Internet-enabled technologies or applications to buy and sell goods, as well as share information with their business partners (Sila, 2015). The B2C e-commerce model enables businesses to provide goods and services to individual consumers through the Internet (Masoud, 2013;Huseynov & Yildirim, 2016). Examples of B2C activities include online shopping, Internet banking, and online travel services (Huseynov & Yildirim, 2016).…”
Section: E-commerce Business Models and Trendsmentioning
confidence: 99%
“…The B2C e-commerce model enables businesses to provide goods and services to individual consumers through the Internet (Masoud, 2013;Huseynov & Yildirim, 2016). Examples of B2C activities include online shopping, Internet banking, and online travel services (Huseynov & Yildirim, 2016). Whereas B2B e-commerce transactions are between businesses entities, B2C e-commerce transactions are between a firm and the firm's customers.…”
Section: E-commerce Business Models and Trendsmentioning
confidence: 99%